Myocardial infarction – the increasing problem in young people - Masajtis, Anna; Barylski, Marcin; Banach, Maciej; Rysz, Jacek; Drożdż, Jarosław (Przewodnik Lekarza/Guide for GPs, 2006)
Myocardial infarction is a conciliation where we could observe the total occlusion of coronary vessel, supplying the specified area of heart. It usually concerns the coronary arteries previously partially occluded in the course of atherosclerosis. On the basis of many studies finished so far, the frequency of myocardial infarctions in people below 45 years old is about 10% of total number of infarcts. The most of such cases is connected with men, however it has been observed the trend of increase of number of myocardial infarcts also in young women. The latest data have shown that the number of cardiac infarcts in women below 55 years old is about 20%.